Fiqh of Disaster: A Development of Landslide Mitigation-Preparedness Module Based on the Transdisciplinary Islamic Approach - Shalihin, Rahmat Ryadhush; Rosa Bustam, Betty Mauli; Pramudya, Yudhiakto; Suyadi, Suyadi (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThe purpose of this research is to create a non-formal module on the fiqh of disaster as part of an effort in landslide mitigation-preparedness using a community-oriented in Indonesian society. Indonesia is strategically placed in the ring of fire, making the main areas vulnerable to natural disasters. As one of the most prominent Muslim organizations in Indonesia, Muhammadiyah, with fiqh of disaster attempts to provide direction for society on disaster management based on Islamic norms and regulations. In this study, we use a transdisciplinary Islamic approach within the key fields of Islamic education, Islamic jurisprudence, and disaster jurisprudence, and physics (inclined plane). The research method used in this study is R&D under the ADDIE model, with five steps: analysis, design, development, evaluation, and analysis. This study included data document evaluation and questionnaires as data collection, whereby content analysis, product development, and product feasibility are all data analysis methodologies. The results showed that the module on landslide mitigation for society is well executed. The material examiner obtained a total score of 22 with a percentage of 91% and rated it "very valid.” The subject examiner obtained a total score of 13 with a percentage of 81% and rated it "very valid." This study provides recommendations for further Implementation in the form of the effectiveness of modules for the community based on ADDIE phases. In addition, it is hoped that the study can be developed in the post-disaster stage so that researchers, policymakers, the government, and the community in landslide disaster management can use it.                                                   AbstrakTujuan dari penelitian ini adalah untuk membuat modul nonformal fikih kebencanaan sebagai bagian dari upaya kesiapsiagaan penanggulangan tanah longsor dengan pendekatan community-oriented pada masyarakat Indonesia. Letak Indonesia yang strategis di ring of fire membuat wilayah-wilayah utama rentan terhadap bencana alam. Sebagai salah satu ormas Islam terkemuka di Indonesia, Muhammadiyah dengan fikih kebencanaan berupaya memberikan arahan kepada masyarakat tentang penanggulangan bencana berdasarkan norma dan aturan Islam. Dalam studi ini, kami menggunakan pendekatan Islam transdisipliner dalam bidang-bidang utama pendidikan Islam, fikih Islam, fikih kebencanaan, dan fisika (bidang miring). Metode penelitian yang digunakan dalam penelitian ini adalah R&D dengan model ADDIE, dengan lima langkah yaitu analisis, desain, pengembangan, evaluasi, dan analisis. Kajian ini meliputi evaluasi dokumen data dan kuesioner sebagai pengumpulan data, dimana analisis isi, pengembangan produk, dan kelayakan produk merupakan metodologi analisis data. Hasil penelitian menunjukkan bahwa modul penanggulangan longsor untuk masyarakat terlaksana dengan baik. Penguji materi memperoleh skor total 22 dengan persentase 91% dan dinilai “sangat valid”. Penguji mata pelajaran memperoleh skor total 13 dengan persentase 81% dan menilainya “sangat valid.” Penelitian ini memberikan rekomendasi Implementasi selanjutnya berupa efektivitas modul untuk masyarakat berdasarkan tahapan ADDIE. Kajian ini diharapkan dapat dikembangkan pada tahap pascabencana sehingga dapat dimanfaatkan oleh para peneliti, pembuat kebijakan, pemerintah, dan masyarakat dalam penanggulangan bencana tanah longsor.How to Cite Shalihin, R. R., Bustam, B. M. R., Pramudya, Y., Suyadi. (2022). Fiqh of Disaster: A Development of Landslide Mitigation-Preparedness Module Based on the Transdisciplinary Islamic Approach. TARBIYA: Journal of Education in Muslim Society, 9(2), 105-122. doi:10.15408/tjems.v9i1.30159.